The Inhibition Effect of the Expired Esomeprazole on the Corrosion of Carbon Steel in Desalination Water - Gebril, Abdussalam; Bakari, Ibrahim (Journal of Pure & Applied Sciences, 2022)
A study has been carried out to evaluate the effect of expired Esomeprazole (S3O3N19H17C) (20mg) as Inhibitor on the corrosion behaviour of carbon steel in desalination water (Drinking water) by using weight loss technique at room temperature. The test solution used in this study was Desalination water (Drinking water) samples and expired Esomeprazole was used as Inhibitor. The Langelier Saturation Index (LSI) results and the potential pH diagram (Pourbaix diagram) gave an indication that Desalination water sample was a corrosive media. From the study results, it was found that all the weights of the tested specimens were decreased. Furthermore, the results of the carbon steel specimens that were tested in present of inhibitor showed that the weight loss and corrosion rate decreased as the weight of inhibitor increased. The maximum efficiency was found 52.08% when the weight of inhibitor was 2.0055g which was the maximum weight and the minimum corrosion rate was 0.0046cm/year. So, it was assumed that the expired Esomeprazole has good inhibition effect on the corrosion of carbon steel.